Checklist and distribution of lady beetles (Coleoptera: Coccinellidae) in Iran - Rahim Abdolahi Mesbah; Jamasb Nozari; H. Allahyari; M. Zare Khormizi (Iranian Journal of Animal Biosystematics, 2016)
This paper is an attempt to fill all of previous literature of coccinellidae records and species distribution in different provinces of Iran. Distribution was extracted for each species from literatures. There are 6 subfamilies, 16 Tribes, 32 genus and 117 species in Iran. The largest subfamily, tribe and genus in Iran were Scymninae, Scymnini and Scymnus, respectively. The most distribution was for species Hippodamia variegate (Goeze), Coccinella septempunctata L., Oenopia conglobata L., Chilocorus bipustulatus L. and Adalia bipunctata L.